Wheel tracking test (WTT) conducted under different standards : Study and correlation of test parameters and limits - Morea, Francisco (2015)
The wheel tracking test (WTT) is an important tool to define asphalt mixture rutting performance. In this study, the rutting behaviour in the WTT was compared under two different standards, BS 598-110 and EN 12697-22 small size device procedures. A significant number of mixtures were studied considering different volumetric characteristics, binder types and test temperatures. The relationship between calculated test parameters in both standards is discussed. Similar deformation rate responses in mixtures using both test methods were observed. A correlation between the calculated parameters rutting rate of BS 598-110 and wheel tracking slope (WTS) of EN 12697-22 was obtained. Possible WTS limits are discussed, considering previous experience in the WTT according to BS 598-110 and the relations obtained with the low shear viscosity of the binders.